Impact of country governance dimensions to the microfinance institutions' efficiency - Nazratul Aina Mohamad Anwar; Fakarudin Kamarudin; Hafezali Iqbal Hussain; Khar Mang Tan; Nurazilah Zainal (Inderscience Publishing, 2024)
The main purpose of this study is to examine the impact of two dimensions of country governance namely: 1) voice and accountability; 2) political stability and absence of violence to the social efficiency and financial efficiency of microfinance institutions (MFIs). Besides, this study also investigates the potential of MFIs specific characteristics and macroeconomic that may influence MFIs' efficiency. The present study gathers data on a total of 142 MFIs from the Philippines and Indonesia over the period 2011 to 2017. Overall, the results implied that, during the period of the study, although the MFIs had been operating on a relatively optimal scale, they were managerially inefficient to exploit their resources to the fullest in the view of both social efficiency and financial efficiency. This information could be useful to several parties and have several implications for MFIs, policymakers, investors and researchers to improve the efficiency level of MFIs.